The Financial Supply Chain Management: a New Solution for Supply Chain Resilience - Virgil Popa (Amfiteatru Economic Journal, 2013)
In the present article, the author aims to find solutions to optimize the supply chain for the cash flow – a flow of products reversed from the physical one and the two-ways flow of information. In the last 15-20 years, academics and practitioners were oriented towards increasing the speed, cost reduction on supply chain material's flow, oriented towards 3RP (3 Resource Planning) logistics solutions and management solutions such as outsourcing or collaborative management. In terms of information flow, there has been a real revolution with the rise of the Internet and information technology standards introduced by the VICS (Voluntary Interindustry Commerce Standards), CSCMP (Council of Supply Chain Management Professionals), SCC (Supply Chain Council) şi ECR Europe (Efficient Consumer Respons). The objective of this paper is to identify new ways of working together on supply chain financial flows. Methods used are the documentation in the literature and the practices of transnational companies under recession. Results refer to the identification of new solutions such as reverse factoring. A comparative analysis regarding the european and national regulations gets us to the conclusion that Romania is still tributary to traditional commercial credit. We propose that the Collaborative management, as a modus vivendi in a globalized and super computerized world, must be included within all Romanian organizations life, within the Supply Chain, but also those which are 3PL (Third Part Logistics) and 4PL (Four Part Logistics) organizations, where not only information services are included, but also financial services (banks and specialized financial institutions).
Keywords: M19; M11; G32; 330; Financial supply chain management; logistic chain; working capital; supply chain finance; net working capital; factoring; reverse factoring